Help-seeking behavior among miscarrying women with and without post-miscarriage health problems in Ghana. - Samuel Kwaku Essien; Batholomew Chireh; Peter Kwabena Essien (Public Library of Science (PLoS), 2023)
Understanding how frequently women seek assistance after experiencing a miscarriage could potentially help address unmet needs in managing post-miscarriage health problems (PMHP). However, most studies focus primarily on the causes and effects of PMHP and neglect the influence of help-seeking behavior on PMHP. This study examined help-seeking behavior among women who have experienced a miscarriage in Ghana, whether they sought help from healthcare professionals or not, and the impact it had on post-miscarriage health problems (PMHP). The study analyzed subsample data (N = 1,843) from the 2017 Ghana maternal health survey of miscarrying women aged 15-49 years who answered questions on help-seeking after a miscarriage from 900 clusters in ten administrative regions of Ghana, using a two-stage stratified cluster probability sampling design. The study used chi-square and modified Poisson with Generalized Estimating Equations (GEE) to examine help-seeking behavior among miscarrying women in Ghana and its impact on post-miscarriage health. The PMHP prevalence was 13.5% (95% CI: 12.0-15.1). Of the 1,843 women, 76.2% (95% CI: 74.3-78.2) sought help following a miscarriage, with 73.6% receiving help from healthcare professionals, 4.6% from non-healthcare professionals, and 21.8% receiving help from both groups. Help-seeking behavior was associated with factors such as education, place of residence, marital status, distance to a health facility, and money for treatment. Women who sought help had a 3.0% (Adjusted Prevalence Ratio, (aPR = 0.97, 95% Cl: 0.95-0.99) reduced prevalence of PMHP compared to those who did not seek help after controlling for other factors. Encouraging more women to seek help following a miscarriage could play a critical role in reducing PMHP, which can substantially improve their physical well-being. This finding highlights the need for more health education programs that address potential barriers in women at higher risk of miscarriage-related complications, including those aged ≥ 31 years, from seeking help after a miscarriage.